Pengaruh Aktivitas Tanggung Jawab Sosial Perusahaan, Kinerja Perusahaan dan Likuiditas Terhadap Agresivitas Pajak Perusahaan Manufaktur yang Terdaftar di BEI Periode 2013-2019 - Monika Sari Br Purba; Malik Maulana (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
This study aims to examine the effect corporate social responsibility activities, corporate performance and liquidity on the tax aggressiveness of manufacturing companies listed on the Indonesia Stock Exchange for the period 2013-2019.The sample selection method uses purposive samplingon companies listed on the IDX for the period 2013-2019.The analytical method used is multiple linear regression with the SPSS 21 program. The test results show that corporate social responsibility activities have a negative effect on corporate tax aggressiveness,corporate performance has a positive effect on tax aggressiveness, and liquidity has a positive effect on tax aggressiveness.